13. KNOWLEDGE OF NURSING STUDENTS REGARDING ANAPHYLAXIS: A CROSS-SECTIONAL STUDY IN HO CHI MINH CITY (Tạp chí Y học Cộng đồng, 2024)
Background: Anaphylaxis is a rapidly occurring allergic reaction that is recognition of the early life-threatening signs if not treated promptly. However, little is known about the level of knowledge of nursing students caring for patients with this condition in hospitals. Nursing research synthesizes the evidence to improve their knowledge and provide a reference for optimizing teaching methodologies used to implement undergraduate teaching in nursing curricula.Objective: This study aimed to explore the knowledge of anaphylaxis and related factors of nursing students at Nguyen Tat Thanh University in Ho Chi Minh City.Method: In this cross-sectional study, a total of 407 nursing students participated. Data collection was started in December 2023 and completed by March 2024.Results: Among the nursing students, 40.3% of them experienced a good level of knowledge regarding anaphylaxis, while 59.7% were at a poor level. The Chi-square test shows that there is a relationship between the current academic year (p < 0.05) and students’ knowledge of managing anaphylaxis. In addition, the number of patients in nursing care per day was a predictor of knowledge in nursing students (r=0.571, p < 0.05).Conclusion: In summary, students have unsatisfactory knowledge regarding anaphylaxis. Specifically, there is still a knowledge gap that can positively affect practice. It is recommended that universities focus on nursing students’ knowledge of managing anaphylaxis and modify the curriculum to enhance their practices in this field.
Keywords: knowledge; anaphylaxis; nursing students